Uncovering the indispensable role of women in nurturing resiliency: Evidence from MSMEs in Denpasar - Ida Ayu Nyoman Saskara; Ni Putu Wiwin Setyari (Faculty of Economics and Business, University of Muhammadiyah Malang, 2022)
This study aims to explore the economic resilience of the families of women MSMEs actors in Denpasar City during the pandemic. Non-proportional random sampling was used to select samples, and binary logistic analyzes were used to analyze the data. This study reveals that women actors in MSMEs show greater economic resilience than men. We argue that the finding related to the work ethics of Balinese women that deeply rooted in their cultural beliefs.